Meningkatkan Kemampuan Mengenal Geometri Melalui Permainan Menebak Bentuk Gambar Segitiga, Persegi, Persegi Panjang dan Lingkaran Menggunakan Media Audio Visual - Jeconya E. Lengkong (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to improve the ability to recognize geometric shapes in Santa Theresia Tomohon Catholic Kindergarten. This type of research is a type of classroom action research with research subjects set at Santa Theresia Tomohon Catholic Kindergarten teachers with a total of 9 children, consisting of 4 boys and 5 girls. The research method used is PTK (Classroom Action Research). Data collection methods used are observation, documentation, and interviews. This research was conducted in two cycles with each cycle consisting of four stages, namely planning, observing, and reflecting. The technique of data analysis in research is action process analysis (qualitative) carried out in collaboration on reflection based on the data collected. Analysis of the results of the action (quantitative) was carried out to analyze the data in the form of a score, which is the result of the ability of the learning outcomes of the ability to recognize geometric shapes through audio-visual media, analyzed by calculating percentages. The results showed that in cycle 1 of 9 children, only 33.33% of children achieved the mastery indicator, then after conducting action research in cycle 2 of 9 children, 100% achieved the mastery indicator with an increase of 66.67%. Based on the results of the study, it can be concluded that the activity of guessing pictures of geometric shapes (triangles, squares, rectangles and circles) through audio-visual media is a suitable activity to improve children's ability to recognize geometric shapes in children.